Identification of Mount Sirung Geothermal Potential based on Land Surface Temperature and 3D Gravity Model - Ayu Alvita Primastika; Dhika Faiz Fadrian; Fardhan Rafshan Zani; Nanda Ridki Permana (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
According to the Ministry of Energy and Mineral Resources 2021 data, first ranks in the list of 10 provinces with the lowest electrification ratio in Indonesia. One of the geothermal prospect areas in East Nusa Tenggara is Mount Sirung. This research was conducted in August 2022 which aims to identify geothermal systems. Gravity data was obtained from the GGMPlus 2013 with a total of 3819 data. Land Surface Temperature (LST) is used as supporting data with a surface temperature approximately 26.1 – 29.5°C because there are manifestations of hot springs at Mount Sirung. Based on the derivative analysis, there are four trajectories in the northwest-southeast direction with reverse faults and normal faults as the geothermal control system of Mount Sirung. The results of 3D gravitational inversion modeling are estimated that there is clay interspersed with breccia with a density of 2.34 – 2.39 g/cm3 as clay cap at 0 – 600 m, and lava interspersed with sandy tuff as a reservoir with a density of 1.98 – 2.03 g/cm3 at 700 – 1400 m. Based on these results and discussions, Mount Sirung is proven to have geothermal potential which can be utilized as a source of electrification in East Nusa Tenggara.